Peningkatan Kemampuan Penalaran Matematika Dengan Pendekatan Saintifik Terintegrasi Pada Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT)(PTK Pembelajaran Matematika Kelas VIII Semester Genap SMP Negeri 1 Teras Tahun 2015/2016) - Haryadi, Didik, Drs. Ariyanto, M.Pd (2017)
The purpose of this study is to describe the efforts of Improving the ability of mathematical reasoning with the subject of students of class VIII D SMP Negeri 1 Teras academic year 2015/2016 with an integrated scientific approach model NHT. This study includes the type of classroom action research. Techniques of collecting data through observation methods, tests, field notes, and documentation. Data analysis techniques through the flow method that includes three components of data reduction, data presentation and withdrawal of conclusions (data verification). The validity of data using triangulation of investigators. The result of the research shows the increase of reasoning ability seen from 1) the students in submitting initial guess before the action of 12 students (37,50%) after the action become 28 student (87,50%), 2) the student in finding pattern before action of 6 student (18,75%) after action to 24 students (75,00%), 3) students in mathematical manipulation before the action of 9 students (28.12%) after action to 22 students (68.75%) and 4) students in drawing conclusions before action 5 Students (15.63%) after action to 21 students (65,62%) Based on the above description concluded that the application of integrated scientific approach on NHT can improve the ability of mathematical reasoning.